Taking lead from the community: What do young people living with HIV want us to research? - Arish Mudra Rakshasa-Loots; Kaylee S van Wyhe; Shalena Naidoo; Ntuthu Daizana; Barbara Laughton; Tembela Boyana (Public Library of Science (PLoS), 2023)
Priority setting workshops enable researchers to take the lead from people with relevant lived experience, and design research which authentically responds to community needs. Large-scale global priority setting exercises have previously identified key research questions related to paediatric and adolescent HIV treatment, prevention, and service delivery. However, priority setting workshops focused on the needs of young people living with HIV are lacking in southern Africa. Here, we report the outcome of a priority setting workshop organised in Cape Town, South Africa with 19 young people living with HIV and their parents and caregivers. Workshops were facilitated by trained research and clinical staff, who provided a plain-language introduction to research questions for the attendees. During the day-long workshop, attendees developed a list of research questions concerning HIV-related physical health, mental health, and psychosocial support and later voted on the order of importance for the questions which they had collectively identified. Facilitators did not prompt any questions or amend the phrasing of questions generated by the attendees. A cure for HIV was highlighted as the most important research priority for young people living with HIV. Other priorities for young people included the effects of antiretroviral therapy on the body, the brain, and their social relationships, causes of emotional issues such as depression and mood swings, and potential interventions to reduce HIV-related stigma in schools through positive education for teachers and students. Research priorities for parents and caregivers included improving antiretroviral adherence through long-acting injections, mental health impacts of HIV status disclosure without consent, and improving support provided by local community clinics. The research questions identified through this workshop may be used by researchers to develop future studies which truly benefit young people living with HIV in South Africa and beyond.